(untitled) (Development Engineering Conferences Center Articles Database, 2025)
This research focuses on the synthesis, characterization, and catalytic evaluation of defect-engineered chromium-based MOFs, specifically MIL-101-Cr. Defects were introduced into the structure using benzoic acid as a modulator throughout the solvothermal synthesis method. The study explores the impact of these structural modifications on the catalytic efficiency of MIL-101-Cr in CO₂ fixation reactions. Comprehensive characterization techniques, including XRD, SEM, BET, FTIR, and TPD, were utilized to analyze the structural, morphological, and thermal properties of the defective MOFs. Catalytic tests revealed significant improvements in CO₂ conversion and epoxide ring-opening reactions, with the defective MOFs achieving a conversion rate of up to 90% under optimized conditions. These findings emphasize the promise of defect-engineered MIL-101-Cr as a highly efficient catalyst for sustainable CO₂ utilization, contributing to advancements in green chemistry and environmental remediation.